The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/cm070117n
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Molecular Structure to Field-Effect Mobility:  The Investigation of Side-Chain Functionality in Phenylene−Thiophene Oligomers and Their Application in Field Effect Transistors

Abstract: Short conjugated phenylene (P)−thiophene (T) oligomers with varying α and ω alkyl and alkoxy substitutions were synthesized using Stille and Suzuki coupling reactions to investigate the correlation between end-group structure and electronic properties on P2TP and P3TP conjugated cores. Several soluble oligomers were synthesized with 5,5‘-bis(4-n-octylphenyl)-2,2‘-bithiophene (do-PTTP) showing the highest mobility (μ = 0.18 cm2 V-1 s-1) and on/off ratio of 107 at a substrate temperature of 50 °C. Thin film morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…Organic Semiconductors: All of the semiconductor materials used were synthesized in house as described elsewhere [26,27], and purified by sublimation using a three-temperature zone furnace (Lindberg/Blue Thermo Electron Corporation, White Deer, PA) at a reduced pressure of 10 À6 Torr (1 Torr ¼ 133.3 Pa) or less. Surface Modification of Device and Shearing Substrates: For OTS and PTS device substrates we used highly-doped n-type (100) Si wafers (<0.004 V cm) with a 300 nm dry thermal oxide gate dielectric (capacitance C i ¼ 10 nF cm À2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic Semiconductors: All of the semiconductor materials used were synthesized in house as described elsewhere [26,27], and purified by sublimation using a three-temperature zone furnace (Lindberg/Blue Thermo Electron Corporation, White Deer, PA) at a reduced pressure of 10 À6 Torr (1 Torr ¼ 133.3 Pa) or less. Surface Modification of Device and Shearing Substrates: For OTS and PTS device substrates we used highly-doped n-type (100) Si wafers (<0.004 V cm) with a 300 nm dry thermal oxide gate dielectric (capacitance C i ¼ 10 nF cm À2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The syntheses of these materials are reported elsewhere. [26,27] This collection of compounds forms a library suitable to test the generality of the SS method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…0.55 eV whereas the monoalkylated homologues show still an increase of ∆E. Assuming that (i) the situation in the aggregates is a mirror image of the porperties in solid state (thin film) and that (ii) the amount of ∆E is a measure for the intermolecular interaction (packing effects) and thus for electron transport (mobility) properties it is expected that (a) oligomers with linear substituents are much superior to the homologues with branched alkyl chains [27] and (b) improvement of electronic properties might level off at around five to seven thiophene units for electronic applications like OFETs. [28] Figure 5.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…[14] Since the report of the first organic thin-film transistor (TFT), efforts have been made to chemically functionalize the conjugated core, in the hope of elucidating structure-property relationships that have been well-established for inorganic materials. [7,[15][16][17] For example, Garnier and co-workers showed that adding a linear hexyl group at the a-position of sexithiophene (6T) resulted in a 25-fold increase in TFT mobility. [11] This was explained by the ordering that resulted from the natural association of the alkyl side chains and the conjugated core of each molecule with that of its neighbor in the thin film.…”
Section: Introductionmentioning
confidence: 99%